CONSUMERS INTEREST FOR ERGONOMIC KNOCK-DOWN WATER FILTERS - Santoso, Gempur; Wiyarno, Yoso; Poniman (UNIPA PRESS, 2019)
Provision of clean water is still a problem currently in Indonesia , 80% of the population still consume water that does not meet health standards. Is the ergonomic knock down water filters to provide clean water become consumer interest?. The study was designed using a comparative descriptive study, The number of respondents is 30 people who use water filters. Data is taken by observation and questionnaire. Data is analyzed using descriptive percentages. The result of the research shows that the